Combatting Terrorism at Sea: assessing NATO’S maritime operations in the Mediterranean - Shukri, Shazwanis (Universiti Utara Malaysia Press, 2019)
Terrorism via the Mediterranean Sea route is one of the security threats faced by Europe in recent years. The basin recorded a large volume of maritime vessels traversing daily via the major straits and consequently exposed them to the possibility of terrorist attacks. This includes cargo and commercial vessels that carry tons of valuable cargo. There is growing concern that the vessels may be used to support terrorist activities. In light of this, NATO has adopted maritime operations to strengthen sea-patrolling and enhance the security of sea lanes in the Mediterranean. This paper sought to examine the terrorist incidents that occurred in the Mediterranean Sea. The paper then scrutinized the evolution of NATO’s approaches terrorism in the basin from 2001 until 2016 Specifically, this paper analysed the implementation of the Operation Active Endeavour (OAE) which was initiated as an immediate response to the 9/11 terrorist attacks in the United States to fight against international terrorism. The mandate assigned through this operation includes, amongst others, monitoring and surveillance activities, escorting assistance, compliant boarding and joint-training with NATO partners. These tasks have significantly contributed to a sharp decline in terrorist plots in the Mediterranean Sea. This paper obtained its data from textual analysis and interviews with NATO military officers. conclude that maritime operations by NATO play a functional role to hinder the potential of terrorist attacks and effectively maintain the security of the sea lanes.